Peran Pengembangan Kurikulum Merdeka dalam Mewujudkan Pembelajaran Pendidikan Agama Islam yang Efektif - karisma, Yahya (Jurnal Pendidikan Indonesia, 2026)
Abstract. The curriculum plays a central role in the implementation of education as it serves as the primary guideline for the teaching and learning process. Curriculum development is necessary to align the education system with advances in science, technology, and the evolving needs of society. This study aims to examine the role of Merdeka Curriculum development in supporting the realization of effective Islamic Religious Education (PAI) learning. This research employs a qualitative approach using a library research method. Data sources were obtained from various literature, including books, national and international journal articles, official government documents, and previous studies relevant to the topic. Data collection was conducted through documentation techniques, while data analysis utilized content analysis methods. The findings indicate that the development of the Merdeka Curriculum plays a significant role in enhancing the effectiveness of PAI learning through several aspects, namely: (1) learning flexibility that provides teachers with the autonomy to design innovative and contextual learning; (2) the implementation of differentiated instruction that accommodates the needs, interests, and characteristics of learners; (3) character strengthening through the internalization of Pancasila Student Profile values that align with the objectives of Islamic Religious Education; (4) increased active participation and engagement of learners in the learning process; and (5) the development of 21st-century competencies, such as critical thinking, creativity, communication, and collaboration. Furthermore, the Merdeka Curriculum also contributes to improving the professionalism of PAI teachers and optimizing the achievement of student learning outcomes. Nevertheless, the implementation of the Merdeka Curriculum in PAI learning still faces several challenges, including limited teacher understanding of the curriculum concept, insufficient availability of adequate teaching materials, and limited supporting facilities and infrastructure. Therefore, the development of the Merdeka Curriculum must be carried out continuously and supported by synergy between the government, schools, teachers, students, and the community to address educational challenges and support the improvement of PAI learning quality and overall educational standards. This study is expected to provide both theoretical and practical contributions to the development of Islamic Religious Education learning in the current era of educational transformation.